Consumer chronicles : cultures of consumption in modern French literature - Walker, David H., 1947- (Contemporary French and francophone cultures, 2011)
At a time when the world is contemplating the depletion of non-renewable natural resources, the consumer society is increasingly being called into question. This is nowhere more acutely evident than in France, where since its beginnings in the nineteenth century, the consumer revolution, extending market forces into every area of social and private life, has been perceived as a challenge to core elements in French culture, such as traditional artisan crafts and small businesses serving local communities. Cultural historians and sociologists have charted the increasing commercialisation of everyday life over the twentieth century, but few have paid systematic attention to the crucial testimony provided by the authors of narrative fiction. Consumer Chronicles rectifies this omission by means of close readings of a series of novels, selected for their authentic portrayal of consumer behaviour, and analysed in relation to their social, cultural and historical contexts. Walker's study, offering an imaginative interdisciplinary panorama covering the impact of affluence on French shoppers, shopkeepers and society, provides telling new insights into the history and characteristics of the consumer mentality.